"Don't tell me this isn't relevant all over again in its brand new same old way": imagination, agitation, and raging against the machine in Ali Smith's Spring. Issue 3 (2nd July 2020) - Masterson, John
ABSTRACT: This paper explores the third novel in Ali Smith's seasonal quartet, Spring . Using Achille Mbembe's Necropolitics as a conceptual frame, I analyze Smith's rendering of a Britain grappling with Brexit in times of transnational populism. As with Autumn and Winter, Smith's prose is saturated with intertextual borrowings from pop and "high" culture, also interrogating the links between "nanoracism" and the "immunity and community" knot (Dillet). This paper reads Spring alongside Smith's contribution to and advocacy of the Refugee Tales project regarding the diverse discourses surrounding migration, xenophobia, and indefinite detention. Smith's writing traces the darkness of our populist present with its rhetorical and material violence, as well as the possibilities for creative response and resistance. I argue that her seasonal quartet to date and her work with Refugee Tales aesthetically and ethically defend the principle that human dignity, both individual and collective, rests on the ability to tell stories.